2008
DOI: 10.1097/iop.0b013e318171a629
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carcinoma With Orbital Involvement

Abstract: Ocular symptoms and signs may be the initial presentation of recurrent nasopharyngeal carcinoma. One must therefore be aware of possible tumor recurrence in patients with a prior history of nasopharyngeal carcinoma who present with symptoms of tearing or an eyelid mass, as this would enable prompt referral to the oncologist and otorhinolaryngologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
1
18
1
1
Order By: Relevance
“…However, one should differentiate orbital metastasis from orbital extension of NPC. Orbital extension often occurs via the pterygopalatine fossa and inferior orbital fissure, or sometimes through the ethmoid and sphenoid sinuses [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, one should differentiate orbital metastasis from orbital extension of NPC. Orbital extension often occurs via the pterygopalatine fossa and inferior orbital fissure, or sometimes through the ethmoid and sphenoid sinuses [15].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only three case series in the literature have shown cases with ophthalmic complaints as the initial signs of NPC. [ 3 4 5 ] The rest were all individual case reports with unique presentations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] In our literature review, we only found three case series that reported ophthalmic manifestations of NPC tumors before or in association with NPC initial presentation. [ 3 4 5 ] To the best of our knowledge, there were no local similar reports describing ophthalmic complaints as an initial presentation of NPC in our region. In this case series, we describe patients who presented to our ophthalmic practice before being diagnosed with NPC to highlight the most common possible ophthalmic manifestations of NPC tumors that should attract the attention of general ophthalmologists and ocular pathologists to this diagnosis.…”
Section: Introductionmentioning
confidence: 93%
“…In a series reported by Heng et al , only 2.6 per cent of non-disseminated nasopharyngeal carcinoma cases had orbital involvement, and this was reported mainly in cases of recurrent nasopharyngeal carcinoma 2 . Kelvin et al described nine cases of nasopharyngeal carcinoma with orbital involvement; eight of these nine cases had previously been treated for nasopharyngeal carcinoma, with subsequent new orbital relapse 3 …”
Section: Discussionmentioning
confidence: 99%